Efeitos dos diferentes processos de cocção sobre o conteúdo de flavonoides totais no cariru (Talinum triangulare (Jacq.) - SILVEIRA, Luana Karoline Furtado (2023)
The cariru Talinum triangulare Jacq is a vegetable commonly appreciated in Northern Brazil. It is used in dishes as an accompaniment to soups and meat stews, in bean broths, however, its high nutritional potential is underused, so more studies are needed to analyze its potential not only nutritional, but also of bioactive compounds and the action of methods of cooking on these substances. Therefore, the objective of this work is to evaluate the action of different cooking methods on the total flavonoid contents of cariru (Talinum triangulare Jacq). For this, the methodological procedures used followed the internationally recommended and accepted standards. The results of the physicochemical analyzes infer that the leaves in natura have a high content of AW, the pH was basic, the total soluble solids were 0.83 brixº and the total titratable acidity was 0.64. Bioactive analyzes show considerable potential that makes Cariru a good source of these natural compounds. Phenolic compounds, chlorophylls A and B and flavonoids were found in fresh leaves of the vegetable. The study also indicates a significant variation in the values of flavonoids in the different thermal processes performed. The microwave cooking method stood out with an increase of 65%, on the other hand the oven roast cooking method was the only one that decreased the flavonoid values by 27.7%, and the steam cooking method obtained an increase of 26.7%. In short, it was concluded that Cariru Talinum triangulare (Jacq.) is an extremely rich vegetable in bioactive compounds that can be enhanced or minimized by the chosen cooking process.